A retrospective study of outcomes of device-associated osteomyelitis treated with daptomycin. Issue 1 (December 2016) - Hermsen, Elizabeth; Mendez-Vigo, Luke; Berbari, Elie; Chung, Thomas; Yoon, Minjung; Lamp, Kenneth
Abstract Background Daptomycin appears well tolerated and effective for osteomyelitis treatment. However, limited data exist regarding daptomycin use for treatment of device-associated osteomyelitis (DAO). Methods We used a retrospective, observational database (Cubicin® Outcomes Registry and Experience [CORE® 2007–2009]) that assessed patients treated with daptomycin to evaluate the characteristics of patients with DAO, outcomes after daptomycin treatment, and safety of daptomycin in this setting. Information from 54 institutions for patients with prosthetic joint infection (PJI) and other hardware-associated osteomyelitis (OHAO) who received daptomycin from January 2007 to December 2008 with follow-up data in 2009 was collected using a standardized data collection form. Results Eighty-two patients receiving daptomycin were identified in CORE 2007–2009; 48 patients (59 %) had follow-up data. Sixty-seven percent of patients had received a previous antibiotic. Surgical intervention was similar between the 2 groups: PJI, 22 of 27 (82 %) and OHAO, 17 of 21 (81 %). However, device removal or replacement was more frequent in the PJI patients (17 of 27, 63 %) than in the OHAO patients (8 of 21, 38 %). Clinical success was reported in 22 of 27 (82 %; 95 % confidence interval [CI], 62–94 %) patients with PJI and 18 of 21 (86 %; 95 % CI, 64–97 %) patients with OHAO at follow-up (13–402 days). Adverse events occurred in 8 of 50 (16 %) patients in the safety population and did not differ by daptomycin dose. Conclusion Daptomycin appeared effective and well tolerated in patients with DAO, including PJI or OHAO.